An assessment of visual and physical impaired person's preferences to own residential property in urban areas of Kuala Lumpur and Selangor - Nasriah binti Samsudin (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2018)
Owning a residential property provides the sense of security and protection which can lead to happiness, productivity and contentment of one's life. Moreover, residence proprietorship is a way that creates stability and improves the quality of life of the persons with disabilities (PwDs). As Malaysia is approaching the developed country's status and becoming a nation of high-income economy by 2020, the housing industry needs to adapt/be adaptive to the demand of special groups, i.e. persons with disabilities. Everyone has the right to own a good living standard and as to achieve this standard, all people regardless of their physical ability should have access to own a house. Universal houses included the well-planned elements which make the house can be resided by all family members and it incorporates the principle of universal design in providing a comfortable and secure house. The aim of this research is to study on the preferences in owning residential property among the persons with disabilities in Kuala Lumpur and Selangor. This research focused on the main preferences of the housing's location, design and price among the persons with disabilities in owning residential property and the level of satisfaction towards the current location, design and of their residential property. This research was carried out by applying the quantitative approach whereby a questionnaires survey were distributed to 800 of respondents among the persons with disabilities with the main focused is on two categories of disabilities; the physical and visual impairment. The sample size were determined by using Yamane 1973 formula and the surveyed were distributed at NGOs of PwDs, shelter's homes, PwDs seminar and dialogue and also during the tournament of Paralympic. The outcome of this study shows that the PwDs would prefer houses with price range under RM100, 000, encourages the low physical effort and also can be easily access by public transport. It concludes by providing eight (8) recommendation which are to provide special housing subsidies, appointment of potential financial for housing loan, provide “Rent to Own House Program”, “Help to Buy: Shared Ownership” scheme, to provide at least the minimum requirement of universal design in all housing unit, home modification scheme, standardization on the price of low – cost house and also to provide 'One Stop Centre' for housing facilities. This research also will be the reference for providing more information and leading to a better policy formulation as well as a healthier development of housing industry for the persons with disabilities.